Critical involvement of atypical chemokine receptor CXCR7 in allergic airway inflammation. Issue 2 (12th January 2018) - Chang, Hung‐Chih; Huang, Po‐Han; Syu, Fu‐Sheng; Hsieh, Chia‐Hung; Chang, Sunny Li‐Yun; Lu, Jean; Chen, Hui‐Chen
Summary: Trafficking and recruitment of immune cells to the site of inflammation with spatial and temporal synchronization is crucial for the development of allergic airway inflammation. Particularly, chemokines are known to be key players in these processes. Previous studies revealed that the CXCL12/CXCR4 axis plays an important role in regulating allergic airway inflammation. However, the role of CXCR7, a recently discovered second receptor for CXCL12, in regulating airway inflammation has not been explored. Initially, CXCR7 was considered as a decoy receptor; however, numerous subsequent studies revealed that engagement of CXCR7 triggered its own signalling or modulated CXCR4‐mediated signalling. In the present study, we detected the expression of CXCR7 in airway epithelial cells. Use of a lentiviral delivery system to knock down the expression of CXCR7 in the lung of sensitized mice abrogated the cardinal features of asthma, indicating that CXCR7 plays a role in regulating allergic airway inflammation. The activation of mitogen‐activated protein kinase and Akt signalling in response to CXCL12 in the mouse epithelial cell line MLE‐12 was reduced when CXCR7 expression was knocked down. However, either knockdown or overexpression of CXCR7 in MLE‐12 did not affect CXCL12‐mediated calcium influx, indicating that CXCR7 does not modulate CXCR4‐mediated signalling, and that it functions as a signalling receptor rather than a decoy receptor. Finally, we found that the expression of chemokine CCL2 is regulated by CXCR7/CXCL12‐mediated signalling through β ‐arrestin in airway epithelial cells. Hence, regulating the expression of CCL2 in airway epithelial cells may be one mechanism by which CXCR7 participates in regulating allergic airway inflammation. Abstract : Airway epithelial‐CXCR7 is involved in regulating cardinal features of asthma as a signalling receptor, not a decoy receptor, without affecting CXCR4‐mediated signalling. One of the mechanisms by which epithelial CXCR7 regulates allergic airway inflammation might be through regulating the expression of CCL2 during inflammation via β ‐arrestin.